Sosialisasi Pengembangan SDMDalam Meningkatkan Kinerja Karyawanpada Lima Roti Premium BakeryAmbon - Elna Marsye Pattinaja; Senda Leatemia (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Community Service Activities (PkM) to provide outreach on Human Resources (HR) development. This activity was carried out at Lima Roti Premium Bakery Ambon. The method used in this activity is direct socialization and training material, as well as discussions regarding the application of Human Resource Management (HRM) in the development of Human Resources (HR) for managers of Lima Roti Premium Bakery Ambon. Based on the results of activities, good management will produce good Human Resources (HR), who have abilities and skills. All the problems they face will affect the performance of these resources, both physically and psychologically, in achieving a goal. Keywords: HR Development, Employee Performance